Survivor Insight: A Study of Family, Friend, and Community Response to Interpersonal Violence. Issue 4 (21st April 2017) - Todahl, Jeff; Olson, Deborah; Walters, Elaine
ABSTRACT: The purpose of this study was to examine the perspectives of survivors of trauma concerning their family, friend, and community responses to their trauma. Using a community-based, participatory action framework, a measure was developed and distributed to 351 randomly drawn survivors of interpersonal violence. The majority of participants indicated that they were never or rarely helped or protected at the time they first experienced the trauma. Several significant correlations were found between participants' perceptions of their own healing and the responses of people in their lives. Many respondents also indicated that people do not know how to help survivors heal and that the general public does not understand how trauma affects people. The results are discussed within the framework of developing supports for trauma survivors that include trauma-informed family, friends, and community. Questions for further research and implications for professional practice and trauma-informed communities are discussed.